ADAlılar | Issue 3 | January 2021 - Javadov, Samir; Kerimli, Ilham; Huseynova, Rumiyya; Babayeva, Elmira; Ismayilova, Aylin; Guliyev, Mahammad; Zeynalov, Rifah; Allahverdiyeva, Nazli; Alizada, Aylin; Hajiyeva, Fatma; Kazdal, Leyla; Aliyeva, Narmin; et al. (ADA School, 2021)
Dear reader, If you are holding this magazine in your hands and flipping its pages, that means we have met again. Here we are - with our new team, new contributors, new ideas, and new impressions. We have so much to share with you! We won a tremendous victory and liberated our historical lands after thirty years of occupation. We were starving for this victory. We lost thousands of our heroic soldiers. We lost so many brave and pure hearts, full of love and care to our Motherland. They wrote a history of our great nation with their blood. We pay a tribute to our heroes. Everyone has their part in this victory. School students contributed with their care and support to those on a frontline, and to their families. You have probably noticed that this issue of ADAlılar is mainly devoted to Karabakh, its liberation, and things related to this historical event. The school was switched to online learning mode since we have been fighting with another invisible enemy - COVID 19 for almost a year. However, we managed not only to stay safe and healthy, but also we finished the first semester with excellent grades. Yes, studying online has its big disadvantages. But is it that can stop us from learning everyday something new? The school has grown up and almost doubled in size since our last meeting. Many new students have joined our ADA family. We are getting bigger, stronger and smarter. What is more important – now we know that when we really want something, when we believe in our strength and union, nothing is impossible to achieve. This release of ADAlılar is just a little proof that our students can evolve the most with every challenge. Each member of ADAlılar editorial board was a real team player and also excelled as an individual. Thanks to everyone who contributed to this edition! Samir Javadov Editor-in-Chief
Keywords: ADA School -- Magazine